The Use of Social Media by UINSU Students, Faculty of Ushuluddin and Islamic Studies Reviewed from Hadith - Ar Rahman, M Rifai; Harahap, Hotmatua Peralihan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study explores the use of social media among students of the Faculty of Ushuluddin and Islamic Studies (FUSI) UINSU with a phenomenological approach and hadith analysis. Although social media has great potential as a means of learning and digital da'wah, the results of the study show that the majority of students use it more for entertainment. This has an impact on academic productivity, quality of worship, and balance of students' social lives. With data collection techniques through in-depth interviews, observations, and documentation studies, this study identifies factors that influence students' behavior in using social media, and examines the relevance of hadiths related to time management and Islamic digital ethics. The main findings show that uncontrolled use of social media, especially at night, causes sleep pattern disturbances and decreases academic concentration. From an Islamic perspective, hadiths on time management and the importance of maintaining digital communication ethics offer guidance in forming more responsible social media habits. Therefore, this study emphasizes the improvement of Islamic digital literacy and the active role of educational institutions in building students' awareness of the more productive use of social media. This study contributes to the study of Islamic digital literacy and social media-based da'wah strategies, and opens up opportunities for further research on the effectiveness of digital da'wah in shaping student behavior in the digital world.